2019
DOI: 10.26822/iejee.2019450787
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reading Racetracks on the Sight Word Recognition of Four Elementary School Students with Learning Difficulties

Abstract: Many children with different kinds of learning problems struggle with reading. To help them combat their challenges, easy-to-implement interventions are needed. Reading racetracks have proven to be effective tools to increase sight word fluency in students with disabilities. The purpose of this single-case study was to evaluate this technique, for the first time, in a context outside of the United States. Four elementary school children with various learning difficulties received nine to twelve individual inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…The objective of this study was to evaluate the effects of a peertutorial reading racetrack intervention on the word fluency of secondary students with LD and those with a co-morbidity of LD and EBD. In line with other research (e.g., Hyde et al, 2009;Green et al, 2010;Erbey et al, 2011;Hopewell et al, 2011;Grünke, 2019), our results indicate that the reading racetrack intervention described in this paper was very effective in improving students' ability to automate the reading of trained words. This also applies to the long-term effects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The objective of this study was to evaluate the effects of a peertutorial reading racetrack intervention on the word fluency of secondary students with LD and those with a co-morbidity of LD and EBD. In line with other research (e.g., Hyde et al, 2009;Green et al, 2010;Erbey et al, 2011;Hopewell et al, 2011;Grünke, 2019), our results indicate that the reading racetrack intervention described in this paper was very effective in improving students' ability to automate the reading of trained words. This also applies to the long-term effects.…”
Section: Discussionsupporting
confidence: 92%
“…By applying the intervention at the secondary level and with students with LD, as well as students with LD and EBD, our study demonstrates that reading racetrack interventions can be used effectively with a heterogeneous student population. Further, while many previous studies have suggested that the intervention is effective in primary school (e.g., Grünke, 2019), the present study provides evidence that secondary students can benefit from word-level reading interventions as already shown in the meta-analyses by Scammacca et al (2007Scammacca et al ( , 2015. According to the meta-analysis by Hollo et al (2014), particularly students with EBP have had numerous negative experiences in reading and writing, so it is important to balance them with positive learning situations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Racetracks has shown positive effects on reading fluency in several studies (Barwasser et al, 2021;Erbey et al, 2011;Green et al, 2010;Grünke, 2019;Hopewell et al, 2011;Hyde et al, 2009;Sperling et al, 2019 and it can be used with a wide range of learners (Falk et al, 2003), which makes it useful for students in inclusion settings. However, all respective studies used a one-onone teaching approach, unsuitable for inclusive classroom instruction.…”
Section: A Cooperative Game-based Approach To Integrate Repeated Reading Into Regular Inclusive Classroom Instructionmentioning
confidence: 99%
“…Reading skill is foundation for success and contribute significantly to the improvement of cognitive skill, intellectual development, job success, career development, and the ability to respond to change [5]. Conversely, those who fail to acquire adequate reading skill likely face some problems such as dropping out of school, unemployment, and low overall income [6]. Furthermore, students also have problem in writing.…”
Section: Introductionmentioning
confidence: 99%